2013
DOI: 10.1177/1470320312471228
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular remodelling after acute myocardial infarction: Impact of clinical, echocardiographic parameters and polymorphism of angiotensinogen gene

Abstract: Introduction: The development of left ventricular remodelling after acute myocardial infarction is a predictor of heart failure and mortality. The purpose of the present study was to assess whether the polymorphism of angiotensinogen (AGT) gene with threonine (T) instead of methionine (M) at amino acid 235 in exon 2 (M235T) had effects on cardiac remodelling after acute myocardial infarction. Methods: One hundred and forty-one patients (mean age 56.4±11.1 years) with a first acute myocardial infarction were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
4
15
0
2
Order By: Relevance
“…We decided not to apply cut-off values for characterizing the remodeling process; rather, we investigated the diameter changes due to the remodeling between the early and late managed groups. Inflammatory and genetic factors may also play role in remodeling ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…We decided not to apply cut-off values for characterizing the remodeling process; rather, we investigated the diameter changes due to the remodeling between the early and late managed groups. Inflammatory and genetic factors may also play role in remodeling ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies by Balcells et al 23 and Swinburn et al 24 showed a correlation between regional wall-motion abnormalities and the results of perfusion contrast echocardiography assessing the viability of infarcted segments. 10,11,17,26 LV systolic characteristics post-MI can be evaluated by STE, including the myocardium peak systolic magnitude or velocity of different directions (peak systolic strain or strain rate of longitudinal, circumferential, and radial directions), LV mechanical dyssynchrony (SD of time to peak systolic strain), and postsystolic motion (postsystolic strain); however, which parameter can more powerfully predict LVr or clinical prognosis is unknown, particularly in AMI patients treated with late PCI. These techniques are angle independent and can differentiate between active contraction and passive displacement; thus, they are more accurate than Doppler tissue imaging for evaluating the regional function of the LV, 25 and several studies have reported that STE can be used to predict LVr or clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques are angle independent and can differentiate between active contraction and passive displacement; thus, they are more accurate than Doppler tissue imaging for evaluating the regional function of the LV, 25 and several studies have reported that STE can be used to predict LVr or clinical prognosis. 10,11,17,26 LV systolic characteristics post-MI can be evaluated by STE, including the myocardium peak systolic magnitude or velocity of different directions (peak systolic strain or strain rate of longitudinal, circumferential, and radial directions), LV mechanical dyssynchrony (SD of time to peak systolic strain), and postsystolic motion (postsystolic strain); however, which parameter can more powerfully predict LVr or clinical prognosis is unknown, particularly in AMI patients treated with late PCI. Our study showed that only GLS, RS are independent predictors of LVr during 6-9 months follow-up post-AMI, but the dyssynchrony and postsystolic motion of the LV cannot independently predict LVr, and GLS appears to be more powerful for predicting LVr.…”
Section: Discussionmentioning
confidence: 99%
“…В целом показатели размеров и объемов полостей сердца отражают интенсивность и скорость процесса ремоделирования миокарда: чем интенсивнее процессы, тем сферичнее полости сердца [9]. При умеренно выраженной систолической дисфункции ЛЖ отмечаются признаки его умеренной дилатации (увеличение КСО и КДО ЛЖ), при этом в течение некоторого времени сердечный индекс сохраняется в пределах нормальных значений [10]. Кроме того, заслуживают внимания имеющиеся данные о развитии ремоделирования сердца даже, несмотря на выбор оптимальной лечебной тактики у больных ИМ с подъемом сегмента ST -выполнения первичного ЧКВ по экстренным показаниям или тромболитической терапии [11].…”
Section: примечание: чсс -частота сердечных сокращений сад -систоличunclassified